The Outcome of Titanium Elastic Nail in Pediatric Femoral Diaphyseal Fracture in a Tertiary Care Hospital - Affan Tayyab, Babar Jan, Dileep Kumar, Faheem Ahmed, Shakeel Gul, Malik Naveed Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the outcome of titanium elastic nail in pediatric femoral Diaphyseal fracture in a tertiary care hospital. Study Design: A longitudinal study Place and Duration: The Department of Orthopedics, Shaheed Mohtarma Benazir Bhutto Institute of Trauma, Karachi from 5th January 2022 to 4th July 2022. Methodology: A total of 126 Patients with femoral shaft fractures who were hospitalized were included. Through a little incision, an intramedullary nail was pushed into the canal. Union and callus formation were monitored with serial radiographs, and weight bearing was gradually increased based on fracture healing. The chi-square test and stratification were utilized to attain this result. A significance level of 0.05 was used. Results: There were 76.2% male and 23.8% female. The mean nail diameter, radiological union, limb length discrepancy and angulation were 3.31±0.32mm, 8.71±1.44weeks, 1.09± 0.81cm and 5.43±2.63° respectively. The mean follow-up was 4.30±1.06 months. The pain was observed in 15.1% of children while in 66.7% of cases no complications were observed. A total of 66.7% of cases were found with excellent, 18.3% with good and 15.1% with poor outcome. Conclusion: Titanium elastic nails have a high probability of good and excellent outcomes in children and it is a simple, minimally invasive implant technique. Keywords: Outcome, Titanium Elastic Nail, Pediatrics, Femoral Diaphyseal Fracture.